The Influence of Product Quality, Service, and Price on Motorcycle Purchasing Decisions at P.T.Astra Honda Motor Unaaha - Bindarto Bindarto (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2022)
This study aims to determine product quality, service quality, and price effects on motorcycle purchasing decisions at P.T. Astra Honda Motor Unaaha. The population in this study amounted to 35 respondents. The analytical method in this study used validity testing, reliability testing, multicollinearity testing, heteroscedasticity testing, and hypothesis testing. Data analysis was carried out with the help of the SPSS 26 program. The results of this study indicate that the variables of product quality, service quality, and price simultaneously has a significant effect on the variable Decision to Purchase a Motorcycle at P.T. Astra Honda Motor Unaaha, the variable Product Quality partially has a positive and significant impact on the Decision to Purchase a Honda Motorcycle at P.T. Astra Honda Motor Unaaha, the variable Quality of Service partially has a positive and significant effect on the Motorcycle Purchase Decision variable at P.T. Astra Honda Motor Unaaha, (4) the price variable has a positive and significant impact on the decision to purchase a motorcycle at P.T. Astra Honda Motor Unaaha.